Convenient and efficient synthesis of functionalized unsymmetrical Z-alkenyl disulfanes. Issue 18 (7th March 2018) - Musiejuk, M.; Doroszuk, J.; Witt, D.
Abstract : We developed a simple and efficient method for the synthesis of functionalized unsymmetrical Z -alkenyl disulfanes under mild conditions in moderate to good yields. Abstract : We developed a simple and efficient method for the synthesis of functionalized unsymmetrical Z -alkenyl disulfanes under mild conditions in moderate to good yields. The designed method is based on the reaction of Z -alkenyl thiotosylates with thiols in the presence of base. The developed method allows the preparation of unsymmetrical Z -alkenyl disulfanes bearing additional hydroxy, carboxy, or amino functionalities.